Modeling constraints in putting: the ISOPAR method - Stöckl, M.; Lames, M. (International Journal of Computer Science in Sport, 2011)
One of the main theories in ecological psychology is the theory of affordances. Affordances are opportunities for action which are provided by the environment in which the action takes place and are action specific. So affordances describe how the environment allows, supports and constrains an action. The idea of studying the affordances can also be applied to sport, in this case to putting in golf, to gain insight into how performance is influenced by the sport specific environment. During toumaments, discrete experiences of players while performing a putt were collected for several rounds at one green. Using the ISOPAR method (Stöckl et al., 2011) all the single experiences of one round of the different players were transformed into a continuous average experience of the field across the whole green. Based on ISOPAR maps we can visualize the affordances and constraints which influenced the field's play. According to the number and the arrangement of the iso-lines on the ISOPAR maps we can identify areas on the green where the play of the field was constrained heavily by gradients on the green's surface and/or distance to the cup.